Media coverage on environmental issues in Malaysia / Zainoor Sulaiman - Sulaiman, Zainoor (Faculty of Communication and Media Studies (FCMS), 1993)
"Is it really Malaysia against the environment? is Malaysia is the only country in the world selling timber? Is there a dark shroud of noxious fumes and smog constantly blanketing the whole country? are all rivers dead, barely moving water courses overlaid with thick chemical with a thick coat of oily and chemical sludge? Do we need to warn people, just like countries in Europe, not to drink the water issuing from taps? Are we giving way to send dunes and semi-arid scrub-land?" (The New Sunday Times, Aug. 18, 1991)